PENGARUH KOLABORASI PROBLEM BASED-LEARNING DAN MIND MAPPNG, MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR EKONOMI - Ihsan Ihsan; Baiq Salkiah (Media Bina Ilmiah, 2022)
This research is a quantitative quasi experimental non-equivalent control group pretest-posttest design. The technique data analysis used analysis of variance 2 × 2 factorial design (two-way ANOVA) and t test. The results showed that, (1) there is a significant difference in economic learning outcomes between groups of students who study with a collaborative problem-based learning and mind mapping model with a group of students who study using a conventional model, (2) There is a significant difference in economic learning outcomes between groups of students who have high achievement motivation and groups of students who have low achievement motivation. (3) At the level of high motivation there is a significant difference in economic learning outcomes between groups of students who study with a collaborative problem-based learning and mind mapping model is better than the group of students who study with a conventional model, (4)At the level of low motivation there is a significant difference in economic learning outcomes between groups of students who study with a collaborative problem-based learning and mind mapping model is better than the group of students who study with a conventional model, (5) There is a significant interaction effect between the problem-based learning and mind mapping collaborative learning model, achievement motivation on student economic learning outcomes